2018
DOI: 10.3847/1538-4357/aaee65
|View full text |Cite
|
Sign up to set email alerts
|

PALFA Single-pulse Pipeline: New Pulsars, Rotating Radio Transients, and a Candidate Fast Radio Burst

Abstract: We present a newly implemented single-pulse pipeline for the PALFA survey to efficiently identify single radio pulses from pulsars, Rotating Radio Transients (RRATs) and Fast Radio Bursts (FRBs). We have conducted a sensitivity analysis of this new pipeline in which multiple single pulses with a wide range of parameters were injected into PALFA data sets and run through the pipeline. Based on the recovered pulses, we find that for pulse widths < 5 ms the sensitivity of the PALFA pipeline is at most a factor of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…For the surveys that did publish rates, we convert the published rates into rates per survey expressed as the number of FRBs detected per day of observing time. In this paper we adopt R htru ∼ 0.08 FRBs/day (Champion et al 2016), R askap−fly ∼ 0.12 FRBs/day (Shannon et al 2018) and R palfa ∼ 0.04 FRBs/day (Patel et al 2018) and R utmost ∼ 1/63 FRBs/day (Farah et al 2018). These rates encapsulate limits by their survey nature, whether in terms of observing frequency, fluence thresholds, sky coverage or any other selection effects.…”
Section: Frb Detection Ratesmentioning
confidence: 99%
“…For the surveys that did publish rates, we convert the published rates into rates per survey expressed as the number of FRBs detected per day of observing time. In this paper we adopt R htru ∼ 0.08 FRBs/day (Champion et al 2016), R askap−fly ∼ 0.12 FRBs/day (Shannon et al 2018) and R palfa ∼ 0.04 FRBs/day (Patel et al 2018) and R utmost ∼ 1/63 FRBs/day (Farah et al 2018). These rates encapsulate limits by their survey nature, whether in terms of observing frequency, fluence thresholds, sky coverage or any other selection effects.…”
Section: Frb Detection Ratesmentioning
confidence: 99%
“…The refurbished Molonglo Observatory Synthesis Telescope (MOST), utilised for the UTMOST project, has also detected a number of FRBs, most recently reported by Farah et al (2019), as has the Parkes Radio Telescope, most recently reported by Bhandari et al (2018). The Green Bank Telescope (GBT) has reported one FRB (Masui et al 2015) and Arecibo has reported two FRBs (Spitler et al 2014;Patel et al 2018). In all these cases, localisation precision is low.…”
Section: Introductionmentioning
confidence: 98%
“…After about one decade, more than 60 FRBs have been found by terrestrial radio telescopes [2] 1 . FRBs have anomalously high dispersion measures (DMs), significantly exceeding the expected Milky Way contribution along the line of sight, which is contrary to Galactic pulsars [3,4,5,6,7,8,9,10] (but note that low DM has also been hinted from two FRBs [11,12] and a candidate (FRB 141113) [13]). It indicates that FRBs are of extragalactic or even cosmological origin, rather than of Galactic origin [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 93%